Pengelolaan Ikan Pelangi Arfak ( Melanotaenia arfakensis Allen, 1990) Berbasis Aspek Bioekologi (Kasus Pada Beberapa Sungai di Kabupaten Manokwari) - Mariance Y. Kaliele; Roni Bawole; Irma E Kawulur (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2018)
The aim of this research is to study the bioecological aspect of Arfak Rainbowfish, distribution long-wieght frequency and management of endemic arfak rainbow fish in Manokwari. This study conducted for five months from 7 September 2015 to 9 Januari 2016. Fish sample were collected from Prafi river, Nimbai river and Aimasi river and brought to fisheries laboratory. The method of this research is descriptive methode with field observation. The result of water quality parameters are temperature average 30.01oC±1,06oC, flow rate is slow 0.92±0,12, the pH 7,80±0,12, oxygen solute 5,38±0,24, average biological oxygen demand for Prafi river 4 mg/L, Nimbai river 3.1 mg/L, Aimasi river 5.2 mg/L and chemical oxygen demand for Prafi river 8.3 mg/L, Nimbai river 14.2 mg/L dan Aimasi river 7.4 mg/L. Long-weight relation shows that the growth is alometric negative (b<3). The management that could be done is reboisation and management of catching that should not be done at the time fish is mature or ready to mate.